Surgical and local therapeutic concepts of oligometastatic pancreatic cancer in the era of effective chemotherapy - Niesen, Willem; Neoptolemos, John P.; Hackert, Thilo (European surgery, 2019)
SummaryBackgroundPancreatic cancer (PC) remains a disease characterized by an extremely poor prognosis, which is often limited by advanced tumor stage at diagnosis. As surgery remains the only option for long-term survival, indications for resection to achieve a complete tumor removal have been extended in recent years, including locally advanced as well as metastatic disease.MethodsHere, we provide a literature overview of modern multimodal treatment concepts of metastatic PC focused on surgery and local interventions including neoadjuvant concepts, stratification of patients, prognostic parameters, and oncological outcomes.ResultsThe current literature lacks level I evidence studies on surgery in stage IV PC. The available observational studies show that resection for liver metastasis has been increasingly performed in recent years, outcomes improve after neoadjuvant therapy, and certain prognostic parameters can identify patients who benefit from this approach. In addition, interventional or radio-oncological liver-directed therapies have been evaluated showing the possibility of some disease control. Resection of pulmonary metastases is rarely performed, although this patient subgroup may have a more favorable prognosis than patients with stage IV liver cancer. Surgery in the setting of peritoneal carcinomatosis remains experimental without any valid supporting data.ConclusionsThere are promising data to support resection of metastatic PC, presuming this approach is embedded in a multimodal oncological concept with modern and effective multi-agent chemotherapies and proper patient selection. Based on this, future studies should specify distinct groups of patients who benefit from extended surgical approaches including synchronous or staged metastasectomy.
Gesehen am 19.06.2019